(untitled) - Rothke, Ben. (New York, 2005)
Securing corporate resources and data in the workplace is everyone's responsibility. Corporate IT security strategies are only as good as the employee's awareness of his or her role in maintaining that strategy. This book presents the risks, responsibilities, and liabilities (known and unknown) of which every employee should be aware, as well as simple protective steps to keep corporate data and systems secure. Inside this easy-to-follow guide, you'll find 20 lessons you can use to ensure that you are doing your part to protect corporate systems and privileged data.The topics covered include: Phishing and spyware; Identity theft; Workplace access; Passwords viruses and malware'; Remote access; E-mail; Web surfing and Internet use; Instant messaging; Personal firewalls and patches; Hand-held devices; Data backup; Management of sensitive information; Social engineering tactics; and, Use of corporate resources. Ben Rothke, CISSP, CISM, is a New York City-based senior security consultant with ThruPoint, Inc. He has more than 15 years of industry experience in the area of information systems security and privacy.
Keywords: Computer security,Data protection,Bảo vệ máy tính,Bảo mật dữ liệu